Infantile virilisation caused by an androstenedione-producing adrenal adenoma - Oliver McCallion; Krithi Ravi; Darren Fowler; Shaun Wilson; Kokila Lakhoo (Elsevier, 2019)
A previously well fifteen-month-old female infant presented to a district general hospital in the United Kingdom with a three-month history of virilisation developing facial acne, coarse pubic hair, labia majora hypertrophy, menstruation, and clitoral enlargement. A functional adrenal tumour was suspected, supported by raised androgen metabolites on urinary steroid profile. An abdominal ultrasound scan identified a unilateral left adrenal mass. A subsequent CT scan of her chest, abdomen, and pelvis for surgical planning and tumour staging confirmed the left adrenal mass, a normal right adrenal gland, and identified a 3 mm left upper lobe lesion of the lung. The infant underwent a transperitoneal left adrenalectomy and developed adrenal insufficiency post-operatively. Histopathological examination of the adrenal mass confirmed a well encapsulated cortical adenoma with a maximum dimension of 45 mm and weight of 9.8 g. The virilisation symptoms improved following surgical excision and she commenced adrenal replacement therapy. Keywords: Adrenocortical adenoma, Paediatric surgery, Paediatric oncology, Endocrine disorders of childhood, Androstenedione, Functional adrenocortical neoplasia, Virilisation in childhood